Laboratory Investigation Into the Effect of the Storage Capacity of a City Block on Unsteady Urban Flood Flows. Issue 4 (4th April 2023) - Mejía‐Morales, Miguel Angel; Mignot, Emmanuel; Paquier, André; Proust, Sébastien
Abstract: The increasing occurrence of urban flooding in recent years demands a more accurate flood hazard assessment. Therefore, a better understanding of the predominant hydraulic processes in urban flood flows is required. The present paper reports an experimental study conducted in a laboratory scale model, which represents an urban area consisting of a rectangular city block and four surrounding streets. The objective is to quantify the impact of open areas within the city block on the key features of floodwaters. Tests are carried out under unsteady flow conditions, by using three inflow hydrographs with different unsteadiness levels. For each inflow hydrograph, the space available for floodwater volume storage within the block (storage capacity, ϕ ) is varied, keeping the boundary conditions unchanged. A case where the city block has no space for floodwater storage (i.e., ϕ = 0) is used as a reference case. The results indicate that the unsteadiness level of the inflow hydrograph, especially during the rising stage, has a strong influence on the floodwater volume stored within the city block. The increase in storage capacity within the city block leads to a reduction of the global peak outflow discharge, a decrease in flow depths and a local increase in velocities in some streets and within the city block. Finally, with these variations in floodwater features, the level of risk to pedestrians is also impacted, increasing locally when the storage capacity of the block increases. Key Points: Access facilities to buildings and empty spaces within city blocks can modify the flood risk for the inhabitants of an urban area The block storage capacity can reduce flow depths by up to 13% and increase velocities by up to 20% in the streets for the tested cases The inflow hydrograph unsteadiness level has a strong influence on the floodwater volume stored in the block and thereby on the flood flows